ANALYSIS OF TRANSFORMATIONAL LEADERSHIP STRATEGIES IN IMPROVING TEAM PERFORMANCE AT BUMDES FOR VILLAGE ECONOMIC EMPOWERMENT - Chandrasari, Farika; Hidayat, Agus Rohmat; Budiwidodo, Sidik; Suherli, Eli (Politeknik Siber Cerdika Internasional, 2024)
This research aims to analyze transformational leadership strategies in improving team performance in Village-Owned Enterprises (BUMDes), with a focus on village economic empowerment. Effective internal communication is essential to build a solid team within BUMDes, which serves to drive village economic growth. This research uses a descriptive qualitative approach to explore how transformational leadership is applied in BUMDes and its impact on team performance and village economic empowerment. The results show that the four main dimensions of transformational leadership-idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration-play an important role in creating a productive and harmonious work environment. Leaders who serve as role models, communicate a clear vision, provide intellectual stimulation, and show individualized attention to team members are able to increase loyalty, morale, and innovation. This research recommends that BUMDes develop leadership training and strengthen internal communication to support the sustainability of village economic empowerment.